Strategies for achieving efficiency in the general practitioner's everyday life - Kok-Wing Giang; Josefine L. Lilja (Taylor & Francis Group, 2022)
AbstractObjective To describe concrete, effective strategies used by experienced GPs to achieve time efficiency, increase patient satisfaction and maintain high medical quality during patient meetings.Design Qualitative observation yielded field notes for qualitative content analysis according to Graneheim and Lundman. Follow-up telephone interviews were conducted to get feedback from patients.Setting A normal working day with patient meetings in a primary health care center in Sweden.Subjects Five GPs known for being experienced and well-functioning clinicians were strategically chosen to participate in an observational study during patient meetings. Afterwards a random selection of 25 patients (five from each GP) were asked to rate their experience of their meeting.Results Observation and analysis of GPs' work before, during, and after patient meetings revealed several concrete strategies, which we classified into two main categories: Behavioral and Communicative, comprising nine and seven subcategories, respectively.Conclusion Most important behavioral skills for time efficiency were a GP's ability to handle interruptions, and effective administration. Medical quality during patient meetings was most supported by GP continuity and relationship, an exploratory patient-centered approach, a focus on one task at a time, and the ability to acknowledge and learn from medical uncertainty. Patients were most satisfied with GPs who had good communicative skills, good GP continuity and relationship.Key pointsThe changing field of general medicine requires general practitioners (GPs), to work efficiently, but studies on effective work strategies for GPs are scarce.GPs used several concrete strategies falling into two broad categories (behavioral and communicative) that may also be important for other practitioners wishing to improve their methods in clinical patient work.The most important strategies for time efficiency were mainly behavioral; for medical quality during patient meetings, a mix of behavioral and communicative; and for patient satisfaction, communicative.